I Read the News Today, Oh Boy: The Effect of Crime News Coverage on Crime Perception and Trust - Daniel Velásquez; Santiago Medina; Gustavo Yamada; Pablo Lavado; Miguel Nú\~nez; Hugo Alatrista; Juandiego Morzan (Institute of Labor Economics (IZA), 2018)
Crime perception has increased in Peru in recent years, as in other developing and developed countries, in spite of the reduction in crime victimization figures. Our hypothesis is that the news industry is in part responsible for such developments. Using a novel database of written news, we identify short-term deviations from the long-term trend in the coverage of crime news at the province level and estimate the effect of news media on crime perception. We measure coverage as a function of the area an article occupies in cm2. Peruvians are great consumers of written news. For instance, Trome, a Peruvian gazette, is the most read Spanish-language newspaper in the world. We find that a spike of negative crime news increases people's perception about the probability of being a crime victim. We find the opposite for positive crime news. However, the effect per cm2 of negative news is more than three times larger than the effect of positive news in absolute value, signaling a potential asymmetry in the revision of people's expectations. We show that these changes in perception are smaller for recent crime victims than for non-victims and that women's perception is less sensitive to positive crime news. We also explore how these perception changes are transmitted to the political landscape and how individuals distribute accountability and reward between different political institutions.
Keywords: D83; D84; L82; 330; expectation; crime; newspaper; information